Integrating MOOCs in Blended-Learning Courses: Perspectives of Teachers and Students - Bao, Hui; Zhao, Xin (Learning Technologies and Systems, 2021)
Being recognized by Chinese universities, the MOOC has been currently applied in higher education institutions, and has been widely believed as an important opportunity for educational practices. However, only a few teachers have quickly adapted toward MOOC teaching in China. This research highlights the experiences perceived by students’ blended learning in their computer courses, as well as the specific challenges that teachers encounter in blended teaching. This study adopts a mixed-method approach. Relevant data include those generated from email interviews with university teachers (n = 12) and from online questionnaires with students (n = 96) in a Chinese university. The results suggest that both from teachers and students’ perspectives, the effect of application of blended teaching is satisfactory, as it improves classroom teaching in general. Students’ learning interests and their self-study and analytical abilities are likewise improved. Moreover, this research highlights the challenges of teachers based on several aspects – educational technology, teaching content design, students’ participation, and integration of online and offline course contents. The paper concludes with pertinent suggestions for blended teaching, such as finding a balance amongst the three aspects of technology, science, and humanities amidst a constant improvement of the teaching methods.